Challenges facing interventions to promote equity in the early years: exploring the 'impact', legacy and lessons learned from a national evaluation of Children's Centres in England. (2nd January 2023) - Sammons, Pamela; Sylva, Kathy; Hall, James; Evangelou, Maria; Smees, Rebecca
ABSTRACT: This paper discusses the challenges facing a national evaluation of an early years intervention programme, Sure Start Children's Centres (SSCCs), that was implemented across England in the first decade of the 21st century. The paper describes the rationale for the evaluation's mixed methods research design and the ecological theoretical approach adopted. It investigates the SSCC policy aim of combatting the 'impact' of multiple disadvantage on outcomes for families, parents and children. Based on a clustered sample (2, 600 families) it provides evidence of statistical effects for different user groups, including non-users. It points to the complexities in evaluation in non-experimental interventions where there was an emphasis on services to meet local needs and where families could choose which services to access and change patterns of service use over time. The paper synthesises findings and considers how complex, volatile and uncertain environments affected SSCC provision, particularly linked to a change of government and austerity policies after 2010. The paper identifies lessons learned, explores implications for future early years interventions in uncertain times, and proposes alternative approaches to evaluation (a realist approach based on mixed methods and theoretically driven models) where randomised experimental designs are inappropriate for the evaluation of certain complex policies.